Newcastle Disease Virus Detection from Chicken Organ Samples Using Reverse Transcriptase Polymerase Chain Reaction - Lehgarubini Shanmuganathan; Dito Anggoro; Michael Haryadi Wibowo (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2017)
Newcastle disease (ND) is a systemic, viral respiratory disease that is acute and easily transmitted which affects various types of poultry, especially chickens. Diagnosis of ND which generally involves virus isolation and subsequent identification with serological assays has limitations that needs more time. This research was aimed to detect Newcastle Disease virus (NDV) in chickens suspected with ND using the Reverse Transcriptase-Polymerase Chain Reaction (RT-PCR) technique. Nine chicken organ samples such as lien, trachea, and lungs were collected from chicken farms diagnosed with ND. The organ samples were processed and the targeted viral RNA was extracted using the RNA extraction kit. Genome amplification was performed with RT-PCR using specificprimers to target the F gene. Amplification results produced an amplicon product of 565 base pairs (bp). PCR product samples were then visualised using agar gel electrophoresis and viewed using the unified gel documentation system. Amplification results show nine samples positive for the DNA bands corresponding to the targeted band of the NDV F gene fragment. The results of this research confirm that the RT-PCR method is applicable for NDV detection from chicken organ samples.